Socially desirable responding: Enhancement and denial in 20 countries - HE, Jia (Institutional Knowledge at Singapore Management University, 2015)
This article investigated the dimensionality, measurement invariance, and cross-cultural variations of social desirability. A total of 3,471 university students from 20 countries completed an adapted version of the Marlowe–Crowne scale. A two-dimensional structure was revealed in the pooled sample, distinguishing enhancement (endorsement of positive self-description) and denial (rejection of negative self-description). The factor structure was supported in most countries; medium-sized item bias was found in two denial items. In a multilevel analysis, we found that (a) there was more cross-cultural variation in denial than enhancement; (b) females tended to score higher on enhancement whereas males tended to score higher on denial; (c) the Human Development Index, an indicator of country socioeconomic development, was the best (negative) predictor of denial; and (d) both enhancement and denial seemed to be associated with country-level values and personality pertinent to “fitting in.” We conclude that social desirability has a positive and a negative impression management dimension that are meaningfully associated with country-level characteristics, and we argue that social desirability is better interpreted as culturally regulated response amplification.